2010
DOI: 10.1002/asia.200900499
|View full text |Cite
|
Sign up to set email alerts
|

Rare‐Earth Oxide Nanostructures: Rules of Rare‐Earth Nitrate Thermolysis in Octadecylamine

Abstract: The decomposed regularity of rare-earth nitrates in octadecylamine (ODA) is discussed. The experimental results show that these nitrates can be divided into four types. For rare-earth nitrates with larger RE(3+) ions (RE=rare earth, La, Pr, Nd, Sm, Eu, Gd), the decomposed products exhibited platelike nanostructures. For those with smaller RE(3+) ions (RE=Y, Dy, Ho, Er, Tm, Yb), the decomposed products exhibited beltlike nanostructures. For terbium nitrate with a middle RE(3+) ion, the decomposed product exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 44 publications
0
17
0
1
Order By: Relevance
“…法, 得到了多种不同类型的稀土基纳米材料, 这其中包 括稀土的氧化物(RE 2 O 3 ) [13,14] , 氟化物(REF 3 ) [15,16] , 氟氧 化物(REOF) [17] , NaREF 4 型氟化物复盐 [18~21] , 氯氧化物 (REOCl) [22] , 硫氧化物(RE 2 O 2 S) [23] , NaRES 2 型硫化物复 盐 [24] 等. 在已发展出的合成方法中, 一类重要方法是高 沸点有机溶剂中的前驱体热分解法.…”
unclassified
“…法, 得到了多种不同类型的稀土基纳米材料, 这其中包 括稀土的氧化物(RE 2 O 3 ) [13,14] , 氟化物(REF 3 ) [15,16] , 氟氧 化物(REOF) [17] , NaREF 4 型氟化物复盐 [18~21] , 氯氧化物 (REOCl) [22] , 硫氧化物(RE 2 O 2 S) [23] , NaRES 2 型硫化物复 盐 [24] 等. 在已发展出的合成方法中, 一类重要方法是高 沸点有机溶剂中的前驱体热分解法.…”
unclassified
“…Our data showed that the production rate of ROS (such as O 2 •− , H 2 O 2 ) in the spleen of mice by intraperitoneal injection of Ln 3+ at dose of 20 mg/kg was significantly elevated ( Table 2), indicating that the spleen suffered oxidative stress. It is interesting that Ln caused elevated level of cellular ROS although Ln ions were previously thought to be scavengers of free radicals in vitro [35][36][37]. The reasons for the generation of ROS are not understood.…”
Section: The Interaction Between H 2 O 2 and Omentioning
confidence: 98%
“…In recent years, oxide-based nanocomposites have emerged as promising materials for highly efficient catalysts because the interaction between the oxide and other components often results in an improved catalytic performance. [25][26][27] In particular, cerium oxide (CeO 2 ), one of the most attractive rare-earth oxides, has been as ignificant active component of nanocompositesb ecause of its high oxygen-storage capacity ande xcellent catalytic activity. [28][29][30] CeO 2 has am ixed oxidation state (Ce 3 + ,C e 4 + )a nd exhibits strong redox behavior by switching betweent hese two states, which is analogoust ot he catalytic cycle of natural redox enzymes.…”
Section: Introductionmentioning
confidence: 99%